Preparation and characterization of PCM from Glauber salt recoverable from the disposal of lead batteries - De Paola, Maria Gabriela; Arcuri, Natale; Calabrò, Vincenza; De Simone, Marilena (My University, 2016)
Glauber salt (sodium sulfate decahydrate) is a promising phase change material (PCM) to use in the building sector, thanks to the high enthalpy of fusion associated with a proper phase transition temperature. Also it offers economic and environmental advantages because it can be obtained as by product from the disposal process of lead batteries. However the Glauber salt, due to phenomena of phase segregation and subcooling, cannot be used in the pure state but requires the addition of rheological modifiers and nucleating agents. In this work the thermal performances of mixtures based on Glauber salt with different compositions are compared by using T-history method, by adopting sonication for mixing, and following the same preparation procedure for all the samples. Fixed the composition, also the effects of the sequence of addition of the reagents is examined. The analysis carried out by Turbiscan allowed to identify the kinetic of destabilization of each sample and revealed the need to specify in detail the preparation stages of PCM in order to make the composition reproducible in laboratory and on a wider scale.
art n° 024, XVI° Congresso Nazionale CIRIAF, Assisi (Italy), 7-9 April 2016
INPATH-TES, "PhD on Innovation Pathways for TES", H2020-LCE-2014-2, GA 657466
Keywords: Glauber salt; PCM; T-history; Turbiscan